Fenomena likuidasi perbankan AS pada harga saham perbankan di Indonesia - Melan Militia Christania Mea; Dheana Revalina Tewu (Manajemen Bisnis dan Keuangan Korporat, 2023)
The issue of bank liquidation in the US during March 2023 has become a trending topic throughout the world's capital markets, including Indonesia. The objective of this study is to examine whether stock prices in the banking sector in Indonesia are still within the confidence interval during the phenomenon of the US banking liquidation. This study finds that the average share price of the privately controlled banking sector tends to decline in value during the US bank liquidation issues. In addition, other evidence also shows that the issue of liquidation of US banks tends to cause the average price of banking shares controlled by the government to fluctuate.